Regenerative potential of concentrated growth factor compared to platelet-rich fibrin in treatment of necrotic mature teeth: a randomized clinical trial - Taghreed Salah; Wael Hussein; Heba Abdelkafy (BDJ Open)
Abstract Aim This study aimed to compare the potential of two regenerative endodontic procedures, platelet-rich fibrin (PRF) and concentrated growth factor (CGF), in the treatment of mature permanent teeth with necrotic pulps and periapical radiolucency. Methods This randomized clinical trial was written according to the Preferred Reporting Items for Randomized Trials in Endodontics 2020 guidelines. The study was registered in the Clinical Trials Registry ( ClinicalTrials.gov ) with identifier number NCT06227533. Eighteen patients with mature necrotic maxillary incisors with periapical lesions were randomly divided into two groups, one group received treatment with PRF (n = 9), while the other received CGF (n = 9). Radiographs were taken at the beginning, 6 and 12 months after treatment, and confirmed with CBCT to assess periradicular healing. An electric pulp tester and cold test were used to determine whether pulp sensibility had been regained during the follow-up period. The statistical analysis used an independent t-test to compare different groups. Repeated measures ANOVA to compare pre-operative, after 6 months, and after 1 year in the same group. Results Both groups experienced a considerable increase in healing at 6 and 12 months compared to baseline, with no significant differences seen regarding lesion size (p-value was 0.34) and relative bone density (p-value was 0.27). There was no substantial change in the tooth sensibility reading between both groups at 6 months (p-value = 0.34), After 1 year, both groups exhibited identical patterns. Conclusion Revascularization using PRF or CGF successfully preserved mature teeth with necrotic pulps.